Modified concrete recycled fine aggregate and preparation method thereof
By heating and reacting recycled fine aggregates with a modified nano-polyimide and nano-cobalt carbonate composite, the method addresses the high water absorption and performance variability of recycled aggregates, enhancing their mechanical properties and stability for concrete and mortar applications.
Patent Information
- Application Number
- CN202411326215.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
AI Technical Summary
The high water absorption rate and varying performance of recycled fine aggregates from construction waste, such as waste concrete and bricks, hinder their resource utilization and large-scale application due to issues with physical and chemical modification methods.
A method involving stirring, washing, and sieving recycled fine aggregates, followed by mixing with modified nano-polyimide, heating in a closed space at 400-600°C, and reacting with nano-cobalt carbonate to form a composite that fills pores and improves adhesion, reducing water absorption and enhancing mechanical properties.
The method significantly reduces the water absorption rate and increases the mechanical strength of recycled fine aggregates, improving their performance and stability for use in concrete and mortar.
Smart Images

Figure BDA0005055485240000051 
Figure BDA0005055485240000061 
Figure BDA0005055485240000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of comprehensive recycling of solid wastes, and particularly relates to a modified concrete recycled fine aggregate and a preparation method thereof. Background Art
[0002] In 2023, the output of construction waste in my country exceeded 3.2 billion tons, and it showed an increasing trend year by year. Improper handling of construction waste will occupy a large amount of land resources, pollute groundwater, and seriously affect the environment and life and production safety. Therefore, the resource utilization of construction waste is becoming more and more urgent. At present, waste concrete and waste bricks account for more than 80% of construction waste. Therefore, the key to realizing the resource utilization of construction waste lies in the utilization of construction solid waste such as waste concrete and waste bricks. Preparing waste concrete into recycled aggregate is an important way to realize its resource utilization. However, there are major problems in the utilization of recycled aggregates, mainly because the quality of recycled fine aggregates is unstable and the performance varies greatly.
[0003] The main components of recycled fine aggregate made from waste concrete are sand and concrete hydration product powder, most of which are sand particles wrapped or semi-wrapped by calcium silicate hydrate. The pores and irregular shapes in calcium silicate hydrate are the main reasons for the increase in water absorption of recycled fine aggregate, and high water absorption is an important factor affecting the performance of recycled fine aggregate. Therefore, how to reduce the water absorption of recycled fine aggregate and improve the performance of recycled fine aggregate is an important factor affecting the resource utilization and large-scale application of recycled fine aggregate.
[0004] At present, the optimization methods and technical measures for recycled fine aggregate mainly include physical modification and chemical modification. Among them, physical modification is to destroy the weak recycled fine aggregate particle attachment layer or remove the residual slurry adhering to the surface of recycled fine aggregate by crushing, ball milling, physical heat, radiation, etc., so as to reduce the water absorption rate and improve the mechanical properties. However, this method is easy to produce new cracks and new weaknesses, and its modification effect is limited; chemical modification is to plug and fill the pores by adding cement slurry, active substances, salt substances, etc., but due to its large particle size, the filling effect is limited and the reinforcement effect is not good; the second is to corrode the surface attachment layer by acidic substances, etc., but this method is also easy to cause corrosion to the aggregate, and the removal effect is not good. Therefore, it is crucial to adopt an effective method to effectively reduce the water absorption rate of recycled fine aggregate and improve the mechanical properties of recycled fine aggregate to realize the resource utilization and large-scale utilization of recycled fine aggregate. Summary of the invention
[0005] In view of the problem of high water absorption of recycled fine aggregate in the prior art, the present invention aims to provide a modified concrete recycled fine aggregate and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] The first aspect of the present invention provides a method for preparing recycled fine aggregate for modified concrete, comprising the following steps:
[0008] (1) Stir the recycled fine aggregate, then wash and sieve out the powder with a particle size of less than 0.075 mm, and dry it;
[0009] (2) adding modified nano-polyimide to the dried recycled fine aggregate and mixing them evenly to form a recycled fine aggregate mixture;
[0010] (3) The recycled fine aggregate mixture is placed in a closed space, stirred evenly at a rotation speed of 50 to 100 r / min, heated to 400 to 600° C. while maintaining stirring, reacted for 2 to 3 hours, and then cooled to room temperature to obtain modified concrete recycled fine aggregate.
[0011] The modified nano-polyimide is prepared by heating the nano-polyimide to 300-390° C. under hot air conditions, melting the nano-polyimide to form a liquid state, and then blowing nano-cobalt carbonate into the nano-composite particles to form the modified nano-polyimide.
[0012] The hot air condition scatters the nano-polyimide in a fixed space through wind force to prevent it from falling to the ground.
[0013] The preparation temperature of the modified nano-polyimide is 300-390°C, in order to ensure that the nano-polyimide is melted to form a liquid, and then the nano-cobalt carbonate is blown in. The cobalt carbonate loses its crystal water within this temperature range but has not yet decomposed, and can be adsorbed with the nano-liquid polyimide to form nano-composite particles.
[0014] Preferably, the mass ratio of nano-polyimide to nano-cobalt carbonate is (3-5):1.
[0015] More preferably, the mass ratio of nano-polyimide to nano-cobalt carbonate is 4:1.
[0016] Preferably, the particle sizes of nano-polyimide and nano-cobalt carbonate are both less than 1 μm.
[0017] Preferably, in step (2), the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:(2-4).
[0018] More preferably, in step (2), the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:3.
[0019] As a preference, the specific process of cooling in step (3) is: first naturally cool down to below the melting point of nano-polyimide and then open the closed space to quickly cool down to room temperature.
[0020] The melting point of the nano polyimide is 280-333°C.
[0021] Preferably, the stirring time in step (1) is 20 to 40 minutes.
[0022] The stirring time is 20 to 40 minutes in order to remove the easily falling calcium silicate hydrate coating and some sharp edges on the surface. The stirring time should not be too long to avoid producing too much powder.
[0023] The second aspect of the present invention provides a modified concrete recycled fine aggregate prepared by any step of the preparation method of the first aspect.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention places a mixture of recycled fine aggregate and nano-polyimide in a closed space and controls the temperature to react at 400-600°C. At this temperature, calcium silicate hydrate loses water to form a dehydrated phase, which increases its activity. Polyimide forms a liquid and quickly penetrates into the gaps and pores of calcium silicate hydrate. The polyimide fills the pores and has water repellency, thereby reducing the water absorption rate of the recycled fine aggregate.
[0026] (2) In the present invention, a modified nano-polyimide formed by a composite of nano-polyimide and cobalt carbonate is added to the recycled fine aggregate. The carbon dioxide released by the decomposition of cobalt carbonate reacts with the residual calcium hydroxide in the cement slurry to form calcium carbonate, which further fills the tiny gaps and improves the adhesion between the recycled fine aggregate and the hydrated calcium silicate. The cobalt oxide and the like produced by the decomposition of cobalt carbonate have good filling properties, thereby improving the high-temperature stability and corrosion resistance of the recycled fine aggregate and improving the stability of the overall performance of the recycled fine aggregate.
[0027] (3) The crushing index and mortar water demand ratio of the modified concrete recycled fine aggregate prepared by the method of the present invention are significantly reduced, and the mortar strength ratio is significantly increased. It has good mechanical properties, low water absorption rate, and high mortar strength. When used in concrete and mortar, the strength of concrete and mortar is significantly improved. DETAILED DESCRIPTION
[0028] The method of the present invention is described in detail below with reference to specific examples.
[0029] Example 1
[0030] A modified concrete recycled fine aggregate, the preparation method thereof has the following specific steps:
[0031] (1) Pour the recycled fine aggregate into a mixer and stir for 20 minutes to remove the calcium silicate hydrate coating layer and some sharp edges that are easy to fall off the surface. The stirring time should not be too long to avoid producing too much powder. Then wash with clean water, sieve out the powder with a particle size of less than 0.075 mm, and dry it;
[0032] (2) adding modified nano-polyimide to the dried recycled fine aggregate, wherein the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:2, and mixing them evenly to form a recycled fine aggregate mixture;
[0033] (3) The recycled fine aggregate mixture is placed in a closed space, stirred evenly at a rotation speed of 100 r / min, and heated to 400°C under continuous stirring for 2 h. Then, the mixture is naturally cooled to 300°C in a closed state, and then the closed space is opened for rapid cooling to obtain modified concrete recycled fine aggregate.
[0034] The preparation method of the modified nano-polyimide is as follows: the nano-polyimide with an average particle size of 305nm is blown away by wind under hot air conditions and then fixed in a space to prevent it from falling to the ground, and the temperature is raised to 390°C to ensure that the nano-polyimide is melted to form a liquid state, and then nano-cobalt carbonate with an average particle size of 50nm is blown in, and the mass ratio of the nano-polyimide to the nano-cobalt carbonate is 3:1. The nano-cobalt carbonate loses crystal water within this temperature range, but has not yet decomposed, and can be mutually adsorbed with the nano-liquid polyimide to form nano-composite particles, namely the modified nano-polyimide. The melting point of the nano-polyimide is 300°C.
[0035] According to the current national standard GB / T 25176, the crushing index, mortar water demand ratio, and mortar strength ratio of the recycled fine aggregate in the modified concrete are tested. The crushing index is an indicator to measure the mechanical properties of the recycled fine aggregate. The smaller the crushing index, the better the mechanical properties of the recycled fine aggregate. The mortar water demand ratio is an indicator to measure the water absorption rate of the recycled fine aggregate. The smaller the mortar water demand ratio, the lower the water absorption rate of the recycled fine aggregate. The mortar strength ratio is an important indicator for evaluating the effect of the use of recycled fine aggregate in mortar and concrete on its mechanical properties. The larger the mortar strength ratio, the more obvious the improvement in the strength of concrete and mortar.
[0036] The crushing index of the recycled fine aggregate raw material is 35.6%, the mortar water requirement ratio is 1.89, and the mortar strength ratio is 0.61.
[0037] The crushing index of the recycled fine aggregate of the modified concrete in Example 1 was measured to be 14.2%, the mortar water requirement ratio was 1.08, and the mortar strength ratio was 1.02.
[0038] Example 2
[0039] A modified concrete recycled fine aggregate, the preparation method thereof has the following specific steps:
[0040] (1) Pour the recycled fine aggregate into a mixer and stir for 40 minutes to remove the calcium silicate hydrate coating layer and some sharp edges that are easy to fall off the surface. The stirring time should not be too long to avoid producing too much powder. Then wash with clean water, sieve out the powder with a particle size of less than 0.075 mm, and dry it;
[0041] (2) adding modified nano-polyimide to the dried recycled fine aggregate, wherein the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:4, and mixing them evenly to form a recycled fine aggregate mixture;
[0042] (3) The recycled fine aggregate mixture is placed in a closed space, stirred evenly at a rotation speed of 50 r / min, and heated to 600°C under continuous stirring for 3 h. Then, the temperature is naturally cooled to 280°C in a closed state, and the closed space is opened for rapid cooling to obtain modified concrete recycled fine aggregate.
[0043] The preparation method of the modified nano-polyimide is as follows: the nano-polyimide with an average particle size of 500nm is blown away by wind under hot air conditions and then placed in a fixed space to prevent it from falling to the ground, and the temperature is raised to 300°C to ensure that the nano-polyimide is melted to form a liquid state, and then nano-cobalt carbonate with an average particle size of 80nm is blown in, and the mass ratio of the nano-polyimide to the nano-cobalt carbonate is 5:1. The nano-cobalt carbonate loses crystal water within this temperature range, but has not yet decomposed, and can be mutually adsorbed with the nano-liquid polyimide to form nano-composite particles, namely the modified nano-polyimide. The melting point of the nano-polyimide is 280°C.
[0044] The detection method is the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 2 is measured to be 14.6%, the mortar water requirement ratio is 1.12, and the mortar strength ratio is 0.98.
[0045] Example 3
[0046] A modified concrete recycled fine aggregate, the preparation method thereof has the following specific steps:
[0047] (1) Pour the recycled fine aggregate into a mixer and stir for 30 minutes to remove the calcium silicate hydrate coating layer and some sharp edges that are easy to fall off the surface. The stirring time should not be too long to avoid producing too much powder. Then wash with clean water, sieve out the powder with a particle size of less than 0.075 mm, and dry it;
[0048] (2) adding modified nano-polyimide to the dried recycled fine aggregate, wherein the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:3, and mixing them evenly to form a recycled fine aggregate mixture;
[0049] (3) The recycled fine aggregate mixture is placed in a closed space, stirred evenly at a speed of 80 r / min, and heated to 500°C while maintaining stirring, reacting for 2.5 hours. Then, the temperature is naturally cooled to 290°C in the closed state, and the closed space is opened for rapid cooling to obtain modified concrete recycled fine aggregate.
[0050] The preparation method of the modified nano-polyimide is as follows: the nano-polyimide with an average particle size of 180nm is blown away by wind under hot air conditions and then fixed in a space to prevent it from falling to the ground, and the temperature is raised to 350°C to ensure that the nano-polyimide is melted to form a liquid state, and then nano-cobalt carbonate with an average particle size of 40nm is blown in, and the mass ratio of the nano-polyimide to the nano-cobalt carbonate is 4:1. The nano-cobalt carbonate loses crystal water within this temperature range, but has not yet decomposed, and can be mutually adsorbed with the nano-liquid polyimide to form nano-composite particles, namely the modified nano-polyimide. The melting point of the nano-polyimide is 333°C.
[0051] The detection method is the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 3 is measured to be 13.8%, the mortar water requirement ratio is 1.02, and the mortar strength ratio is 1.05.
[0052] Example 4
[0053] The difference from Example 3 is that the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:2.
[0054] The detection method was the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 3 was measured to be 14.6%, the mortar water requirement ratio was 1.10, and the mortar strength ratio was 1.00.
[0055] Example 5
[0056] The difference from Example 3 is that the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:4.
[0057] The detection method was the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 3 was measured to be 15.5%, the mortar water requirement ratio was 1.12, and the mortar strength ratio was 0.98.
[0058] Example 6
[0059] The difference from Example 3 is that in the preparation process of the modified nano-polyimide, the mass ratio of the nano-polyimide to the nano-cobalt carbonate is 3:1.
[0060] The detection method was the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 3 was measured to be 14.2%, the mortar water requirement ratio was 1.05, and the mortar strength ratio was 1.01.
[0061] Example 7
[0062] The difference from Example 3 is that in the preparation process of the modified nano-polyimide, the mass ratio of the nano-polyimide to the nano-cobalt carbonate is 5:1.
[0063] The detection method was the same as that of Example 1. The crushing index of the recycled fine aggregate of the modified concrete of Example 3 was measured to be 14.5%, the mortar water requirement ratio was 1.08, and the mortar strength ratio was 0.99.
[0064] Table 1 Performance test of recycled fine aggregate in modified concrete of Examples 1 to 7
[0065]
[0066] It can be seen from Table 1 that in Examples 1 to 7, the crushing index of the recycled fine aggregate of the modified concrete is 13.8% to 15.5%, the mortar water requirement ratio is 1.02 to 1.12, and the mortar strength ratio is 0.98 to 1.05. Compared with the recycled fine aggregate raw material, the crushing index and the mortar water requirement ratio of the recycled fine aggregate of the modified concrete are significantly reduced, and the mortar strength ratio is significantly increased. It has good mechanical properties, low water absorption, and high mortar strength. It is used in concrete and mortar to significantly improve the strength of concrete and mortar.
[0067] Comparative Example 1
[0068] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (2), the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:1.
[0069] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 1 was measured to be 21.7%, the mortar water requirement ratio was 1.76, and the mortar strength ratio was 0.87.
[0070] Comparative Example 2
[0071] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (2), the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:5.
[0072] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 2 was measured to be 19.4%, the mortar water requirement ratio was 1.23, and the mortar strength ratio was 0.82.
[0073] Table 2 Performance test of recycled fine aggregate in modified concrete of comparative examples 1 to 2
[0074]
[0075] From the comparison of Comparative Examples 1 to 2 in Table 2 with Example 3, it can be seen that the addition of modified nano-polyimide can reduce the crushing index of the recycled fine aggregate and the water demand ratio of the mortar, and improve the mortar strength ratio, that is, the mechanical properties of the recycled fine aggregate are improved, the water absorption rate is reduced, and the strength of the mortar prepared with the recycled fine aggregate is improved. From the comparison of comparative examples 1 and 2 with embodiments 3 to 5, it can be seen that when the dosage of modified nano-polyimide is too low, its crushing index increases (the mechanical properties of recycled fine aggregate decrease), the water demand ratio of mortar increases (the water absorption rate increases), and the strength ratio of mortar decreases (the strength of mortar prepared with recycled fine aggregate decreases). This is because the dosage is too low, and the effect of reducing the water absorption rate of recycled fine aggregate is limited, resulting in an increase in the water demand ratio of mortar, and the strength improvement is not obvious enough; when the dosage of modified nano-polyimide is too high, its crushing index increases (the mechanical properties of recycled fine aggregate decrease), the water demand ratio of mortar increases (the water absorption rate increases), and the strength ratio of mortar decreases (the strength of mortar prepared with recycled fine aggregate decreases). This is because the introduction of excessive polyimide will cause the bonding of recycled fine aggregate to cement paste to deteriorate when applied, and the strength of polyimide itself is relatively low, which is not conducive to the strength improvement of recycled fine aggregate. Therefore, selecting an appropriate amount of modified nano-polyimide can improve the performance of recycled fine aggregate.
[0076] Comparative Example 3
[0077] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (3), no space sealing treatment is performed.
[0078] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 3 was measured to be 22.4%, the mortar water requirement ratio was 1.46, and the mortar strength ratio was 0.75.
[0079] Table 3 Performance test of recycled fine aggregate in modified concrete of comparative example 3
[0080] serial number Whether to use closed space Crushing index (%) Mortar water requirement ratio Mortar strength ratio Example 3 yes 13.8 1.02 1.05 Comparative Example 3 no 22.4 1.46 0.75
[0081] From the comparison between Comparative Example 3 and Example 3 in Table 3, it can be seen that the crushing index and mortar water demand ratio of the modified concrete recycled fine aggregate increase, while the mortar strength ratio decreases. This is mainly because without space sealing treatment, polyimide vapor, carbon dioxide and water vapor will overflow under high temperature conditions, resulting in the inability to fill and reinforce the pores of the recycled fine aggregate, and the performance improvement of the modified recycled fine aggregate is limited.
[0082] Comparative Example 4
[0083] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: after stirring evenly in step (3), continuous stirring is stopped.
[0084] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 4 was measured to be 18.6%, the mortar water requirement ratio was 1.42, and the mortar strength ratio was 0.88.
[0085] Comparative Example 5
[0086] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: the stirring speed in step (3) is 200 r / min.
[0087] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 5 was measured to be 16.7%, the mortar water requirement ratio was 1.31, and the mortar strength ratio was 0.89.
[0088] Table 4 Performance test of recycled fine aggregate in modified concrete of comparative examples 4 to 5
[0089] serial number Is stirring continuous? Stirring speed (r / min) Crushing index (%) Mortar water requirement ratio Mortar strength ratio Example 3 yes 80 13.8 1.02 1.05 Comparative Example 4 no 80 35.6 1.89 0.61 Comparative Example 5 yes 200 21.7 1.76 0.87
[0090] From the comparison between comparative example 4 and embodiment 3 in Table 4, it can be seen that stopping continuous stirring after stirring evenly in step (3) will lead to an increase in the crushing index and water demand ratio of the recycled fine aggregate in the modified concrete, and a decrease in the mortar strength ratio; from the comparison between comparative example 5 and embodiment 3, it can be seen that when the stirring speed in step (3) is increased to 200 r / min, the crushing index and water absorption rate of the recycled fine aggregate in the modified concrete increase, and the strength of the mortar prepared with the recycled fine aggregate decreases.
[0091] Maintaining stirring during the preparation of modified recycled fine aggregate can improve the uniformity of nano-polyimide attachment on the surface of recycled fine aggregate, form uniform wrapping of aggregate and penetration of pores, achieve targeted filling of pores, and help improve the structural morphology of the surface of recycled fine aggregate. If stirring is not performed, polyamide amine cannot penetrate and flow, and the filling effect of aggregate gaps will be significantly reduced, and the water absorption rate will be reduced to a limited extent. At the same time, too low a rotation speed or stopping continuous stirring will cause uneven dispersion of modified nano-polyimide under molten conditions, and unreasonable filling of aggregate gaps, while too high a rotation speed will easily cause separation of aggregate and modified nano-polyimide, resulting in enrichment of modified nano-polyimide. Both of the above situations are not conducive to improving the performance of recycled fine aggregate. Therefore, choosing an appropriate stirring speed can improve the performance of recycled fine aggregate.
[0092] Comparative Example 6
[0093] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (3), the temperature is raised to 350°C.
[0094] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 6 was measured to be 16.8%, the mortar water requirement ratio was 1.34, and the mortar strength ratio was 0.82.
[0095] Comparative Example 7
[0096] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (3), the temperature is raised to 750°C.
[0097] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 7 was measured to be 20.2%, the mortar water requirement ratio was 1.68, and the mortar strength ratio was 0.78.
[0098] Comparative Example 8
[0099] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: in step (3), the temperature is not lowered to 290° C., but the closed space is directly opened for cooling after the reaction reaches 2.5 hours.
[0100] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 8 was measured to be 18.2%, the mortar water requirement ratio was 1.58, and the mortar strength ratio was 0.74.
[0101] Table 5 Performance test of recycled fine aggregate in modified concrete of comparative examples 6 to 8
[0102]
[0103]
[0104] From the comparison of Table 5 Comparative Examples 6 and 7 with Example 3, it can be seen that too low or too high reaction temperature will lead to an increase in the crushing index of the recycled fine aggregate of the modified concrete (the mechanical properties of the recycled fine aggregate decrease), an increase in the water demand of the mortar (increase in water absorption), and a decrease in the mortar strength ratio (the strength of the mortar prepared with the recycled fine aggregate decreases). This is because the cobalt carbonate can be guaranteed to decompose and release carbon dioxide at a temperature of 400-600°C, while the polyimide can form a liquid state and has not yet reached the boiling point. Under this condition, the polyimide quickly penetrates into the gaps and pores of the hydrated calcium silicate, and the cobalt carbonate decomposes carbon dioxide (under the conditions of the present invention, the temperature at which the carbon dioxide is decomposed is about 400°C and above), reacts with the cement slurry in the recycled fine aggregate to generate calcium carbonate, further blocking finer pores, while improving the bonding force between the sand and the cement slurry. At the same time, the hydrated calcium silicate forms a dehydrated phase under this temperature condition with good activity, which is conducive to participating in the cement hydration reaction and improving its bonding force with cement. The CoO and Co3O4 generated by the decomposition of cobalt carbonate have good high temperature resistance and corrosion resistance, which improves the high temperature stability and corrosion resistance of the recycled fine aggregate. The polyimide also has a certain water repellency, which effectively avoids the penetration of water and reduces its water absorption rate. In comparative example 6, the reaction temperature is 350°C, and the cobalt carbonate has not yet decomposed and cannot play a reinforcing role; in comparative example 7, the reaction temperature is too high, and the polyimide forms steam overflow, which cannot play a filling and bonding optimization role (the boiling point of polyimide is 638.8°C, and the higher the temperature, the faster it evaporates). Therefore, choosing a suitable reaction temperature can improve the reinforcement of recycled fine aggregate.
[0105] From the comparison of comparative example 8 in Table 5 and embodiment 3, it can be seen that when the closed space is opened directly for cooling after the reaction, the crushing index and water demand of the modified concrete recycled fine aggregate increase, and the strength of the mortar decreases. This is because a large amount of polyimide will form steam overflow and form new voids, which increases the water absorption rate of the aggregate, increases the crushing index, increases the water demand ratio of the mortar, and decreases the strength ratio of the mortar. Therefore, it is necessary to cool down to below the melting point of the polyimide after the reaction to ensure that the polyimide is in a completely hardened state.
[0106] Comparative Example 9
[0107] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that: the nano-polyimide is not modified, and the nano-polyimide and nano-cobalt carbonate are directly mixed in proportion at room temperature and then directly added to the recycled fine aggregate for use.
[0108] It was measured that the crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 9 was 25.2%, the mortar water requirement ratio was 1.77, and the mortar strength ratio was 0.67.
[0109] Comparative Example 10
[0110] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that the ratio of nano-polyimide to nano-cobalt carbonate in the modified nano-polyimide is 1:1.
[0111] It was measured that the crushing index of the recycled fine aggregate of the modified concrete of Comparative Example 10 was 18.4%, the mortar water requirement ratio was 1.39, and the mortar strength ratio was 0.86.
[0112] Comparative Example 11
[0113] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that the ratio of nano-polyimide to nano-cobalt carbonate in the modified nano-polyimide is 10:1.
[0114] It was measured that the crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 11 was 17.7%, the mortar water requirement ratio was 1.45, and the mortar strength ratio was 0.80.
[0115] Table 6 Performance test of recycled fine aggregate in modified concrete of comparative examples 9 to 11
[0116]
[0117] From the comparison of Table 6 Comparative Example 9 and Example 3, it can be seen that by adding nano-polyimide and nano-cobalt carbonate instead of modified nano-polyimide, the crushing index of the recycled fine aggregate of the modified concrete and the water demand of the mortar increased, and the strength of the mortar decreased. This is because the modification in advance can ensure that the nano-polyimide and cobalt carbonate merge and adsorb each other to form a whole. If added separately, the penetration of polyimide and the generation of carbon dioxide by cobalt carbonate are not in the same position, and the carbon dioxide cannot accurately participate in the filling and reinforcement of the gap, and the effect will be worse.
[0118] From the comparison of Comparative Examples 10 and 11 in Table 6 with Embodiments 3, 6 and 7, it can be seen that the ratio of nano-polyimide to nano-cobalt carbonate in the modified nano-polyimide is too high or too low, which will lead to the performance decline of the modified recycled fine aggregate. This is because the excessively high content of cobalt carbonate produces more carbon dioxide, which increases the gas content inside the polyimide in the liquid state, causing the porosity of the recycled fine aggregate to increase; the cobalt carbonate content is too low, and more carbon dioxide gas cannot be produced, and sufficient calcium carbonate cannot be generated, and the role of reinforcement is not obvious enough. Therefore, the performance of the recycled fine aggregate can be improved by selecting the appropriate ratio of nano-polyimide to nano-cobalt carbonate.
[0119] Comparative Example 12
[0120] A modified concrete recycled fine aggregate, the preparation method of which is basically the same as that of Example 3, except that the average particle size of the polyimide is 1.5 μm, and the average particle size of the cobalt carbonate is 1 μm.
[0121] The crushing index of the recycled fine aggregate of the modified concrete in Comparative Example 12 was measured to be 16.2%, the mortar water requirement ratio was 1.48, and the mortar strength ratio was 0.78.
[0122] Table 7 Performance test of recycled fine aggregate in modified concrete of comparative example 12
[0123] serial number Polyimide particle size (μm) Cobalt carbonate particle size (μm) Crushing index (%) Mortar water requirement ratio Mortar strength ratio Example 3 0.18 0.04 13.8 1.02 1.05 Comparative Example 12 1.5 1 16.2 1.48 0.78
[0124] From the comparison of Comparative Example 12 in Table 7 with Example 3, it can be seen that when the polyimide particles are micron-sized and the cobalt carbonate size is micron-sized, the performance of the modified recycled fine aggregate decreases. When the particle size increases, the dispersion is not uniform enough, the dispersion is not uniform in the molten state, the penetration is not sufficient, and the cobalt carbonate is not uniformly adsorbed and dispersed, resulting in performance degradation. Therefore, it is necessary to control the particle size of polyimide and cobalt carbonate to be below 1 μm.
Claims
1. A method for preparing recycled fine aggregate for modified concrete, characterized in that: The following steps are involved: (1) Stir the recycled fine aggregate, then wash and sieve out the powder with a particle size of less than 0.075 mm, and dry it; (2) adding modified nano-polyimide to the dried recycled fine aggregate and mixing them evenly to form a recycled fine aggregate mixture; (3) The recycled fine aggregate mixture is placed in a closed space, stirred evenly at a rotation speed of 50 to 100 r / min, heated to 400 to 600° C. while maintaining stirring, reacted for 2 to 3 hours, and then cooled to room temperature to obtain modified concrete recycled fine aggregate.
2. The preparation method according to claim 1, characterized in that: The modified nano-polyimide is prepared by heating the nano-polyimide to 300-390° C. under hot air conditions, melting the nano-polyimide to form a liquid state, and then blowing nano-cobalt carbonate into the nano-composite particles to form the modified nano-polyimide.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the nano-polyimide to the nano-cobalt carbonate is (3-5):
1.
4. The preparation method according to claim 2, characterized in that: The particle sizes of the nano-polyimide and the nano-cobalt carbonate are both less than 1 μm.
5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the recycled fine aggregate to the modified nano-polyimide is 100:(2-4).
6. The preparation method according to claim 5, characterized in that: The specific process of cooling in step (3) is: firstly, the temperature is naturally cooled to below the melting point of nano-polyimide in a closed state, and then the closed space is opened to quickly cool to room temperature.
7. The preparation method according to claim 1, characterized in that: The stirring time in step (1) is 20 to 40 minutes.
8. A modified concrete recycled fine aggregate prepared by the preparation method according to any one of claims 1 to 7.
